The assesment of biochemical oxygen demand loading from the prawn farm at Santubong - Dayang Sherrynazra, Awang Sharkawi. (Universiti Malaysia Sarawak (UNIMAS), 2004)
This study was carried at a prawn fann at Santubong area. The objectives of this study were to detennine the Biochemical Oxygen Demand (BOD) loadings from the shrimp ponds at different days of cultured. Water samples were collected from stocking to harvesting at two weeks intervals. The BOD level was low at early cultured and increased as the prawn growth. The BOD level was also found to increase with increasing amount of feed given. The estimated BOD loading in this prawn fann was approximately 672 kg per year. Therefore, the estimated BOD loading for a complete cycle ofprawn crop was 335 kg per harvest.